«Hombres sin Dios ni razón»: El bandolerismo valenciano durante los reinados de Felipe IV y Carlos II según los dietarios de la época - Alejandro Llinares Planells (Mélanges de la Casa de Velázquez)
Bandits and oligarchic factions dominated the Kingdom of Valencia in the 17th century, generating a structural, almost daily violence in Valencian society during the Baroque period. In this paper we analyse this phenomenon through the personal diaries that were kept during the reigns of Philip IV and, above all, of Charles II, coinciding with a period when this organised crime was at its peak. In this way, we will study which elements most interested the writers, which bandits appeared most frequently, how the society of the time experienced this phenomenon, how public executions were depicted and what opinion the diarists had about banditry.